2000
DOI: 10.1016/s0736-5748(00)00046-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor and neurotrophin‐3 levels in Alzheimer's disease brains

Abstract: In the present study, we investigated the levels of brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3) in post-mortem brain tissue of Alzheimer's disease (AD) patients, and we observed a significant increase of BDNF concentration in hippocampus and parietal cortex of AD patients, as well as a negative correlation between NT-3 levels and age in hippocampus and putamen of control subjects, and for BDNF in frontal cortex. A defining feature of AD is the post-mortem identification of neuritic plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 30 publications
8
86
0
Order By: Relevance
“…The correspondence of relatively greater activation in multiple right hemisphere regions with equivalent behavioral memory performances supports the notion of compensation through the employment of more bilateral network regions (see network view in Cabeza [9]). In all, support for the compensatory hypothesis has been demonstrated across a whole host of neuropsychological [2,10,27,41] and neuroimaging [3,4,6,22] investigations, as well as with neurochemical [13,17,35], neurotrophic [18], and mitochondrial DNA alterations [33].…”
Section: Resultsmentioning
confidence: 92%
“…The correspondence of relatively greater activation in multiple right hemisphere regions with equivalent behavioral memory performances supports the notion of compensation through the employment of more bilateral network regions (see network view in Cabeza [9]). In all, support for the compensatory hypothesis has been demonstrated across a whole host of neuropsychological [2,10,27,41] and neuroimaging [3,4,6,22] investigations, as well as with neurochemical [13,17,35], neurotrophic [18], and mitochondrial DNA alterations [33].…”
Section: Resultsmentioning
confidence: 92%
“…40-42 It may be that, after an initial decline in memory proficiency following damage to MTL structures, patients in the preclinical stage of AD are able to effectively recruit compensatory brain resources (e.g., frontal and temporal cortical regions important for executive functions and semantic memory) to halt or slow further memory decline for a period of time. A similar compensatory response in certain brain-derived neurotrophic factors 43,44 or cholinergic activity 45 may also attenuate memory changes for a time. Given that adequate cholinergic activity and neurotrophic mechanisms are partly responsible for the maintenance of neuronal function and structural integrity, these findings suggest that, under conditions of progressive neurodegeneration, the MTL stimulates the overexpression of certain cholinergic and neurotrophic factors as a possible mechanism of compensation.…”
Section: Discussionmentioning
confidence: 99%
“…With only one notable exception (Durany et al, 2000), decreased BDNF levels were reported (Phillips et al, 1991;Murray et al, 1994;Connor et al, 1997;Ferrer et al, 1999;Hock et al, 2000;Holsinger et al, 2000;Michalski and Fahnestock, 2003). In all studies reporting decreased BDNF levels, however, late stages of AD were studied in which considerable neuron loss has already occurred (Braak and Braak, 1991;Hof et al, 1999).…”
Section: Changes Of Bdnf Expression In Admentioning
confidence: 99%